Guiding Fiqh Analysis of Crypto Assets: A Proposed Framework - Mohammed, Mustafa Omar; El Amri, Mohamed Cherif; Bakr, Ayman Mohammad (Universitas Islam Negeri Jakarta, 2024)
The emergence of cryptocurrencies has brought about revolutionary changes in financial transactions, offering speed, cost-efficiency, and enhanced privacy without the involvement of traditional intermediaries. Despite these advantages, crypto assets pose several challenges from a fiqh perspective. Firstly, there are discrepancies among researchers attempting to define them. Secondly, technological complexities have led to misunderstandings of their concept. Thirdly, there is a general misconception about their similarity to Bitcoin. Fourthly, there is a notable dearth of comprehensive fiqh studies on the topic. Therefore, this study has adopted a qualitative method to address these four research gaps in extant literature. It has critically reviewed the literature to identify the issues and propose a definition of crypto assets and has categorized them into six types. Content analysis research method was used to develop a conceptual framework for the fiqh analysis of crypto assets. The framework is expected to equip Muslim researchers and jurists with processes, risk analysis methods, and benchmarks to objectively evaluate a given crypto asset. AbstrakKemunculan mata uang kripto telah membawa perubahan revolusioner dalam transaksi keuangan, dengan menawarkan kecepatan, efisiensi biaya, dan peningkatan privasi tanpa keterlibatan perantara tradisional. Terlepas dari kelebihan tersebut, aset kripto menimbulkan beberapa tantangan dari sudut pandang fiqh. Pertama, terdapat perbedaan di antara para peneliti yang mencoba mendefinisikannya. Kedua, kompleksitas teknologi telah menyebabkan kesalahpahaman terhadap konsep mereka. Ketiga, terdapat kesalahpahaman umum tentang kemiripannya dengan Bitcoin. Keempat, masih kurangnya kajian fiqih yang komprehensif mengenai topik ini. Karena itu, studi ini mengadopsi metode kualitatif untuk mengatasi empat kesenjangan penelitian dalam literatur yang ada. Studi ini telah meninjau literatur secara kritis untuk mengidentifikasi masalah dan mengusulkan definisi aset kripto dan mengategorikannya menjadi enam jenis. Metode penelitian analisis isi digunakan untuk mengembangkan kerangka konseptual analisis fiqih aset kripto. Kerangka kerja ini diharapkan dapat membekali proses, metode analisis risiko, dan tolok ukur kepada para peneliti dan ahli hukum Muslim untuk mengevaluasi aset kripto tertentu secara objektif.